Adipositas und kontrollierte ovarielle Stimulation (COH) - Strowitzki, Thomas; Capp, Edison (Gynäkologische Endokrinologie, 2017)
BackgroundObesity in infertile women is an endemic problem and has a direct impact on assisted reproductive technology (ART) treatment, in vitro fertilization (IVF) outcome, pregnancy, and development of children in later life.ObjectiveThe impact of body weight and obesity on controlled ovarian stimulation (COH) for ART and ART outcome is illustrated.ResultsPatients who are obese show a reduced ovarian response to COH, require a higher dose of gonadotropins, and have a reduced oocyte yield compared to normal weight women. Pregnancy and live birth rates are significantly lower, while the miscarriage rate is increased. There is no proven benefit of intramuscular vs. subcutaneous administration route.ConclusionsControlled ovarian stimulation is feasible in obese patients, but is significantly worse compared to normal weight patients. Thus, pretherapeutic weight reduction is urgently recommended, particularly in patients with extreme obesity.
Gesehen am 20.08.2020
Englische Zusammenfassung unter dem Titel: Obesity and controlled ovarian stimulation (COH)